2015 IEEE/ACM 37th IEEE International Conference on Software Engineering 2015
DOI: 10.1109/icse.2015.145
|View full text |Cite
|
Sign up to set email alerts
|

Industry Practices and Event Logging: Assessment of a Critical Software Development Process

Abstract: Practitioners widely recognize the importance of event logging for a variety of tasks, such as accounting, system measurements and troubleshooting. Nevertheless, in spite of the importance of the tasks based on the logs collected under real workload conditions, event logging lacks systematic design and implementation practices. The implementation of the logging mechanism strongly relies on the human expertise. This paper proposes a measurement study of event logging practices in a critical industrial domain. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…Recent work in application logging [25], [65], [64], [21], [49] has shown the efficacy of application logs in program understanding, debugging, and profiling. OmegaLog takes inspiration from those efforts, with the goal of better leveraging event logs during attack investigation.…”
Section: Our Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in application logging [25], [65], [64], [21], [49] has shown the efficacy of application logs in program understanding, debugging, and profiling. OmegaLog takes inspiration from those efforts, with the goal of better leveraging event logs during attack investigation.…”
Section: Our Approachmentioning
confidence: 99%
“…1(d); however, the forensic evidence disclosed by the application itself is not encoded in this graph. That is unfortunate, as recent studies [25], [21], [49] have shown that developers explicitly disclose the occurrence of important events through application logging. Further, we observe that the well-studied problem of dependency explosion [39], [42], [41], which considers the difficulty of tracing dependencies through high-fanout processes, is itself a result of unknown application semantics.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the work by [23] uses a term weighting measurement approach to find faults from syslog. The study [24] adopts a term weighting approach to assess a variety of direct monitoring approaches, such as event logs [25], [26], at reporting the occurrence of operational failures in critical systems. This is the first contribution that investigates the use of term weighting to address security logs: the mentioned works focus on reliability rather than security analysis.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Even though developers have been analyzing logs for decades [31], there exists no industrial standard on how to write logging statements [20,49]. Prior studies often focus on recommending where logging statements should be added into the code (i.e., where-to-log) [76,75], and what information should be added in logging statements (i.e., what-to-log) [59,73,51].…”
Section: Introductionmentioning
confidence: 99%